Intrinsic tryptophan fluorescence spectroscopy reliably determines galectin-ligand interactions - Sindrewicz, Paulina; Li, Xiaoxin; Yates, Edwin A.; Turnbull, Jeremy E.; Lian, Lu-Yun; Yu, Lu-Gang (Scientific reports, 2019)
Galectins are involved in the regulation of divergent physiological and pathological processes and are increasingly recognized to play important roles in a number of diseases. However, a simple and effective way in assessing galectin-ligand interactions is lacking. Our examination of the sequence of all 12 human galectin members reveals the presence of one or more tryptophan residues in the carbohydrate-recognition domains of each galectin. This led us to investigate the possibility that alteration of the galectin intrinsic tryptophan fluorescence could be used in determining the strength of galectin-ligand interactions. One representative member from each of the three subtype galectins, galectin-2 (proto-), galectin-3 (chimera-) and galectin-4 (tandem repeat-type), was selected and analysed for galectin interaction with three ligands of different affinities: galactose, lactose and N-acetyl-lactosamine using tryptophan fluorescence spectroscopy (TFS) and, as a comparison, isothermal titration calorimetry (ITC). Good agreement between TFS and ITC measurements were revealed in ligand bindings of all galectin members. Moreover, TFS detected very weak galectin binding where ITC could not reliably do so. The reliability of TFS in determining galectin-ligand interactions was further validated by analysis of galectin-3 interaction with a semisynthetic ligand, F3. Thus, TFS can be used as a simple, sensitive and reliable way to determine galectin-ligand interactions and also as a drug-discovery platform in developing galectin-targeted therapeutic drugs.